Design and implementation of a stunting consultation application based on extreme programming method: an iterative approach for child health improvement - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
Stunting is a severe and complex child health problem that requires a holistic approach to prevention. This research responds to these problems by developing a stunting consultation application based on the Extreme Programming (XP) method to improve access to information and direct interaction with health experts. The research involved three main stages: data collection, application development, and user acceptance analysis. Data collection involved an in-depth literature review, interviews with pediatric health experts, and surveys and questionnaires to potential users. Application development was conducted using the Extreme Programming Method approach, emphasizing rapid iteration and active client involvement. User acceptance analysis was conducted through the distribution of the app to potential user groups using surveys, interviews, and direct observation methods. The application development resulted in a responsive solution focused on user needs. User acceptance analysis showed high satisfaction, with 87% of users satisfied with the app's functionality. The test results of the features confirmed positive performance and suitability to user needs. This research contributes an innovative application that can be a tool in stunting prevention efforts. This contribution is not only limited to the child health domain but also provides a foundation for applying the Extreme Programming Method in developing technology-based health solutions.